Kompetensi Digital dan Ketangkasan Strategis dengan Mediasi Orientasi Pasar terhadap Kinerja Pemasaran Berkelanjutan di Kalangan UMKM - Rahayu, M.E. Yuni; Sulistyanto, Tri Hadi (DFAME Digital Financial Accounting Management Economics Journal, 2026)
This study examines the influence of digital competence and strategic agility on sustainable marketing performance through the mediating role of market orientation among Micro, Small, and Medium Enterprises (MSMEs) in Purwakarta, Indonesia. Grounded in Market Orientation Capability Theory, the study explores how organizational capabilities contribute to long-term marketing sustainability. A quantitative approach was employed using a cross-sectional survey design. Data were collected from 356 MSME owners, managers, and employees involved in marketing and business development activities. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that digital competence significantly enhances market orientation. Strategic agility also exerts a positive and significant influence on market orientation. Furthermore, market orientation positively affects sustainable marketing performance. The mediation analysis confirms that market orientation significantly mediates the relationship between digital competence and sustainable marketing performance as well as the relationship between strategic agility and sustainable marketing performance. These findings demonstrate that technological capabilities and strategic flexibility contribute to sustainable marketing outcomes through customer-focused and market-responsive organizational practices. The study contributes to the marketing and sustainability literature by providing empirical evidence from MSMEs and offers practical implications for strengthening organizational competitiveness through market-oriented capability development.